2005
DOI: 10.3766/jaaa.16.9.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Signal-to-Noise Ratio on Directional Microphone Benefit and Preference

Abstract: This study examined speech intelligibility and preferences for omnidirectional and directional microphone hearing aid processing across a range of signal-to-noise ratios (SNRs). A primary motivation for the study was to determine whether SNR might be used to represent distance between talker and listener in automatic directionality algorithms based on scene analysis. Participants were current hearing aid users who either had experience with omnidirectional microphone hearing aids only or with manually switchab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 14 publications
8
27
0
Order By: Relevance
“…In contrast, the signal was in front for all four DIR-preferred sites. Taken together, this suggests that the relative intelligibility of the primary talker in the two processing modes was the basis for the preference judgments, consistent with the findings of Walden et al (2005). Given that directional processing is designed to improve the SNR of sounds coming from the front by reducing the level of sounds originating from the sides and/or back, it is reasonable to assume that a signal of interest coming from the side or behind the listener may be more intelligible in the omnidirectional mode.…”
Section: DI Is Sc Cu Us Ss Si Io On Nsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, the signal was in front for all four DIR-preferred sites. Taken together, this suggests that the relative intelligibility of the primary talker in the two processing modes was the basis for the preference judgments, consistent with the findings of Walden et al (2005). Given that directional processing is designed to improve the SNR of sounds coming from the front by reducing the level of sounds originating from the sides and/or back, it is reasonable to assume that a signal of interest coming from the side or behind the listener may be more intelligible in the omnidirectional mode.…”
Section: DI Is Sc Cu Us Ss Si Io On Nsupporting
confidence: 84%
“…Given substantial variability, it may be necessary to program signal processing algorithms, such as DNR and AD, to the requirements of the individual patient. This might be accomplished via learning algorithms that take input from the hearing aid wearer during normal daily use to determine preferred signal processing characteristics across a variety of everyday listening environments (Walden et al, 2005). However, more simple solutions to automatic signal processing strategies such as DNR and AD can be pursued if the same signal processing is generally preferred across listeners for a given acoustic environment.…”
Section: Sumariomentioning
confidence: 99%
“…If the listening context described in a questionnaire is not specific enough, the questionnaire might not be able to determine if a given technology is beneficial. For example, laboratory data have shown that, compared to omnidirectional microphones, the effect of directional microphone hearing aids on speech understanding could be positive, neutral, or even negative, depending on the locations of the talker and noises (Lee et al, 1998; Wu et al, 2013), signal-to-noise ratio (SNR) (Walden et al, 2005), reverberation level (Ricketts and Hornsby, 2003), and availability of visual cues (Wu and Bentler, 2010a, b). Because such detailed contextual information is not available in the questionnaire Abbreviated Profile of Hearing Aid Benefit (Cox and Alexander, 1995) (e.g., “When I am in a crowded grocery store talking with the cashier, I can follow the conversation.”), it is unlikely that this inventory can detect the effect of directional technology in the real world (Ricketts et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Individual directional advantage scores for the 12 participants are listed in Table 1. In a previous study using the same test materials and procedures, 0 dB SNR corresponded to the midpoint of the performance-intensity function and was the condition in which 30 of the 31 participants obtained a directional advantage of at least 15% (Walden et al, 2005). The participants in the current study had mean key word scores of 30.3% (range: 12-47%) and 57.2% (range: 27-86%) for the binaural omnidirectional and binaural directional conditions respectively.…”
Section: Speech Recognition In Noise Testingmentioning
confidence: 76%